Caregivers' compliance with referral advice: evidence from two studies introducing mRDTs into community case management of malaria in Uganda - Sham Lal; Richard Ndyomugenyi; Lucy Paintain; Neal D. Alexander; Kristian S. Hansen; Pascal Magnussen; Daniel Chandramohan; Siân E. Clarke (BMC, 2018)
Abstract Background Several malaria endemic countries have implemented community health worker (CHW) programmes to increase access to populations underserved by health care. There is considerable evidence on CHW adherence to case management guidelines, however, there is limited evidence on the compliance to referral advice and the outcomes of children under-5 referred by CHWs. This analysis examined whether caregivers complied with CHWs referral advice. Methods Data from two cluster (village) randomised trials, one in a moderate-to-high malaria transmission setting, another in a low-transmission setting conducted between January 2010-July 2011 were analysed. CHW were trained to recognise signs and symptoms that required referral to a health centre. CHW in the intervention arm also had training on; malaria rapid diagnostic tests (mRDT) and administering artemisinin based combination therapy (ACT); CHW in the control arm were trained to treat malaria with ACTs based on fever symptoms. Caregivers' referral forms were linked with CHW treatment forms to determine whether caregivers complied with the referral advice. Factors associated with compliance were examined with logistic regression. Results CHW saw 18,497 child visits in the moderate-to-high transmission setting and referred 15.2% (2815/18,497) of all visits; in the low-transmission setting, 35.0% (1135/3223) of all visits were referred. Compliance to referral was low, in both settings < 10% of caregivers complied with referral advice. In the moderate-to-high transmission setting compliance was higher if children were tested with mRDT compared to children who were not tested with mRDT. In both settings, nearly all children treated with pre-referral rectal artesunate failed to comply with referral and compliance was independently associated with factors such as health centre distance and day of referral by a CHW. In the moderate-to-high transmission setting, time of presentation, severity of referral were also associated with compliance, whilst in the low-transmission setting, compliance was low if an ACT was prescribed. Conclusions This analysis suggests there are several barriers to comply with CHWs referral advice by caregivers. This is concerning for children who received rectal artesunate. As CHW programmes continue scale-up, barriers to referral compliance need to be addressed to ensure a continuum of care from the community to the health centre. Trial registration The study was registered with ClinicalTrials.gov. Identifier NCT01048801, 13th January 2010.